The unique role of team games in developing students' English language interactive ability (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the distinct impact of team games on developing students' ability to communicate, negotiate, and problem-solve in English. Through participation in group activities, students not only improve their linguistic skills but also cultivate important social and cognitive competencies. The article  discusses the benefits of collaborative language practice and outlines specific strategies to maximize the effectiveness of team games in language learning.